Long-term risk of vascular events after peripheral bypass surgery - Van Hattum, Eline S.; Tangelder, Marco J. D.; Lawson, James A.; Moll, Frans L.; Algra, Ale (Thrombosis and Haemostasis, 2012)
Patients with peripheral arterial disease (PAD) are at high risk of major ischaemic events. Long-term data of all major ischaemic events in PAD patients are scarce and outdated, especially for patients with severe PAD requiring bypass surgery. Our objective was to define their longterm prognosis and develop a prediction model which quantifies this risk up to a decade after surgery. We conducted a retrospective cohort study in patients from the Dutch Bypass Oral anticoagulants or Aspirin (BOA) Study; a multicentre randomised trial comparing oral anticoagulants with aspirin after infrainguinal bypass surgery. The primary outcome was the composite event of nonfatal myocardial infarction, non-fatal ischaemic stroke, major amputation, and vascular death. Cumulative risks were assessed by Kaplan-Meier analysis and independent determinants by multivariable Cox regression models. From 1995 until 2009, 482 patients were followed for a median period of 7.8 years. Follow-up was complete in 94%. Overall 60% of patients experienced a primary outcome event, of which the majority was a vascular death (30%), followed by major amputations (12%). The primary cause of vascular death was a cardiovascular event (29%), whereas the minority was due to complications directly related to PAD (6%). Within five years after bypass surgery vascular death occurred in about a quarter of patients and within 10 years in nearly half of patients. This was double the rate as for non-vascular death. The primary outcome event occurred in over a third and over half of patients in 5 and 10 years after bypass surgery, respectively. From four independent determinants for the primary outcome event: age, diabetes, critical limb ischaemia, and prior vascular interventions, we developed a risk chart, which systematically classifies the 10-year risks of the primary outcome event, ranging from 25% to 85%. This study provided a detailed insight in the course of PAD long after peripheral bypass surgery and enables individual risk assessment of major fatal and non-fatal ischaemic events by means of cumulative incidences and a risk chart.
Keywords: Atherosclerosis; peripheral artery disease; ischaemia; bypass surgery; prognosis